Urinary Phthalate Metabolites in Common Bottlenose Dolphins (Tursiops truncatus) From Sarasota Bay, FL, USA. Issue 10 (20th October 2018) - Hart, Leslie B.; Beckingham, Barbara; Wells, Randall S.; Alten Flagg, Moriah; Wischusen, Kerry; Moors, Amanda; Kucklick, John; Pisarski, Emily; Wirth, Ed
Abstract: Phthalates are chemical additives to common consumer goods including cleaning products, cosmetics, personal care products, and plastic. Because they are not chemically bound to these products and are widely used, the potential for environmental contamination is significant. Phthalates and their metabolites have been associated with endocrine disruption and reproductive impairment, among other adverse health effects, in laboratory animals and human epidemiologic studies. Common bottlenose dolphins ( Tursiops truncatus ) are vulnerable to environmental pollutants due to their apex position in the food chain, long life spans, and habitat overlap with developed coastal areas. The objective of this study was to quantify phthalate metabolite concentrations in urine collected from bottlenose dolphins in Sarasota Bay, Florida, during May 2016 ( n  = 7) and May 2017 ( n  = 10). Screening of nine phthalate monoester metabolites in bottlenose dolphin urine was performed by liquid chromatography tandem mass spectrometry using methods adapted from those used for analyzing human samples. At least one phthalate metabolite was detected in 71% of the dolphins sampled across both years, with the highest concentrations detected for monoethyl phthalate (MEP; GM = 5.4 ng/ml; 95%CI: 1.3–22.0 ng/ml) and mono‐(2‐ethylhexyl) phthalate (MEHP; GM = 1.9 ng/ml; 95%CI: 1.1–3.2 ng/ml). These data demonstrate exposure to two of the most commonly used phthalates in commercial manufacturing, diethyl phthalate (DEP) and di‐2‐ethylhexyl phthalate (DEHP). This study establishes methods for urinary detection of phthalate metabolites in marine mammals and provides baseline data to address a significant and growing, yet poorly understood, health threat to marine wildlife. Plain Language Summary: For the first time, phthalate metabolites have been detected in the urine of wild bottlenose dolphins. Parent phthalate compounds are common additives to plastics and other products. In humans, phthalate exposure is linked with hormonal and reproductive issues; however, health effects in dolphins are currently unknown. Because dolphins are sensitive gauges of their surroundings, detection of phthalate exposure in these dolphins suggests some level of environmental contamination. Additional research is needed to determine the source of their exposure and whether phthalates may negatively impact dolphin health. Key Points: Phthalate metabolites were found in 71% of bottlenose dolphins sampled in Sarasota Bay, FL Monoethyl phthalate (MEP) and mono‐(2‐ethylhexyl) phthalate (MEHP) were the most common metabolites detected in bottlenose dolphin urine Bottlenose dolphins in Sarasota Bay, FL, are susceptible to phthalate exposure